Hydrophilic surface modification of PDMS for droplet microfluidics using a simple, quick, and robust method via PVA deposition - Trantidou, Tatiana; Elani, Yuval; Parsons, Edward; Ces, Oscar (Microsystems & nanoengineering, 2017)
Polydimethylsiloxane (PDMS) is a dominant material in the fabrication of microfluidic devices to generate water-in-oil droplets, particularly lipid-stabilized droplets, because of its highly hydrophobic nature. However, its key property of hydrophobicity has hindered its use in the microfluidic generation of oil-in-water droplets, which requires channels to have hydrophilic surface properties. In this article, we developed, optimized, and characterized a method to produce PDMS with a hydrophilic surface via the deposition of polyvinyl alcohol following plasma treatment and demonstrated its suitability for droplet generation. The proposed method is simple, quick, effective, and low cost and is versatile with respect to surfactants, with droplets being successfully generated using both anionic surfactants and more biologically relevant phospholipids. This method also allows the device to be selectively patterned with both hydrophilic and hydrophobic regions, leading to the generation of double emulsions and inverted double emulsions. Microfluidics: Patterned channels pave way for new applications A simple, low-cost and versatile technique for making reusable microfluidic devices with patterned channels promises new applications. Microfluidic chips have found use in technologies as diverse as fuel cells and the construction of artificial cell models and organs-on-chip. However, the hydrophobic nature of polydimethylsiloxane (PDMS), which is commonly used in chip fabrication, limits potential applications. This spurred Tatiana Trantidou and her colleagues at Imperial College London and University College London, in the United Kingdom, to make PDMS with a hydrophilic surface by coating microfluidic channels with polyvinyl alcohol immediately after plasma treatment. Their innovative technique enables selective patterning of the channels with defined wettability characteristics, facilitating the production of emulsions, double emulsions and inverse double emulsions. The work could expand the use of microfluidic devices to various applications in pharmaceuticals, food science and synthetic biology.